(untitled) (LEARNing Landscapes, 2011)
Contemporary curricular reform efforts are underway in many countries toward adopting and implementing inquiry-based approaches to teaching and learning on a provincial and national level. Buzzwords associated with inquiry-based pedagogy have been used to express similar ideas in bilingual educational communities, but rarely with a direct one-to-one correspondence.We present and explain the meaning of 10 initial key terms from inquiry in education, in English and French.They represent the beginning steps to guide teachers and curriculum developers who are exposed to both the French and English inquiry traditions to translate ideas and curriculum consistently